Rekontekstualisasi Kosmologi Pawukon Bali melalui Artikulasi Wayang dalam Estetika Card Game Fantasi - Yusa, I Made Marthana; Arthayoga, Ketut Karunia; Yasa, Ngakan Putu Darma (Faculty of Arts and Design, Jakarta Institute of the Arts, 2026)
Faced with a booming digital gaming industry and waning youth interest in traditional values, this study recontextualizes the Balinese Pawukon cosmology through a Wayang-themed fantasy card game design. It aims to articulate the intangible cultural heritage of the Wuku calendar into a popular media format using a design thinking approach. Methods include cosmological and visual attribute analysis of the Pawukon system, the four stages of design thinking (empathize, define, prototype, test), character semiotics analysis, and case studies informing a “Cool Wayang” aesthetic. Mixed-methods testing (n=30 Generation Z playtesters) showed high satisfaction: the majority of respondents strongly agreed that the illustrations were visually appealing. Observations noted players using traditional terminology (e.g., deity names like Yamadipati) during gameplay, demonstrating that the gamification strategy effectively lowered cognitive barriers to complex material. Media experts judged the design successful in combining global appeal with national cultural pride. Conclusion: This approach effectively revitalizes the intangible heritage of the Balinese Pawukon (Wuku calendar) cosmology in a dynamic, relevant way. Key pillars of success include Hall’s theoretical framework, hybrid visual innovation, and educational gamification.